Manipulation of seed coat content for increasing oil content via modulating BnaMYB52 in Brassica napus - Jiang Ye; Xiaowei Wu; Xiang Li; Yuting Zhang; Yuqing Li; Hui Zhang; Jie Chen; Yuyan Xiang; Yefan Xia; Hu Zhao; Zengdong Tan; Liang Guo; et al. (Cell Reports)
Summary: Seed oil is synthesized in the embryo, which is surrounded by the seed coat. However, the genetic and molecular mechanisms of how seed coat development affects seed oil content (SOC) remains less studied. Through genome-wide association studies in Brassica napus accessions, we identify BnaA09.MYB52 transcription factor as a candidate gene underlying ZS11_qSCC.A09. Knocking out BnaMYB52 results in a 7.7%–8.2% reduction in seed coat content (SCC) but a 12.3%–13.4% increase in SOC, whereas overexpression of BnaA09.MYB52 leads to the opposite effects. Intriguingly, BnaA09.MYB52 has predominant expression in seed coat during seed development. BnaA09.MYB52 activates the expression of PMEI14 and BAN. Mutant analyses indicate that the SOC is increased by 4.3%–7.7%, while seed coat thickness shows a 12.9%–22.8% reduction in the ban and pmei14 mutants. Thus, our findings identify the molecular mechanism of MYB52-BAN/PMEI14 modules regulating SCC and SOC and provide a potential target for oil content improvement in B. napus.